A computational study on flow characteristics and energy distribution in a rotating coiled rectangular duct with longitudinal vortex generation - Chanda, Ratan Kumar; Hasan, Mohammad Sanjeed; Alam, Md. Mahmud; Mondal, Rabindra Nath (Journal of Naval Architecture and Marine Engineering, 2021)
Investigation on fluid flow and energy distribution in a rotating coiled rectangular duct (CRD) with differentially heated horizontal walls has been analyzed numerically by using a spectral-based numerical scheme. The system is rotated around the vertical axis in the clockwise direction over the Taylor number (Tr) ranging from 0 to 2000 keeping the other parameters constant as aspect ratio Ar =3, curvature ratio BETA=0.5 the Dean number Dn = 1000 and the Prandtl number Pr = 7.0 (water). To reveal steady solution (SS) curves, we applied path continuation technique and obtained five asymmetric SS curves comprising with 2- to 8-pair cell. A bar diagram is also drawn to visualize, at a glance, longitudinal vortex generation on various curves of steady solutions. To explore unsteady behavior, time-progression analysis is performed and flow characteristics are precisely determined by obtaining phase space trajectory of the solutions. The transient flow demonstrates various stages of physically realizable solutions including chaotic, multi-periodic, periodic and steady-state; and it is found that the number of secondary vortices declines as Tr is increased. Convective heat transfer (CHT) is computed and the corresponding dependence on the flow stages is discussed accurately. Finally, a comparison has been made between the numerical computation and experimental investigations which shows a benchmark agreement.